Hypervirulent Klebsiella pneumoniae in a South African tertiary hospital—Clinical profile, genetic determinants, and virulence in Caenorhabditis elegans - Dingiswayo, Likhona; Adelabu, Olusesan Adeyemi; Arko-Cobbah, Emmanuel; Pohl, Carolina; Mokoena, Nthabiseng Zelda; Du Plessis, Morne; Musoke, Jolly (Frontiers in Microbiology, 2024)
A distinct strain of Klebsiella pneumoniae (K. pneumoniae) referred to as hypervirulent (hvKp) is associated with invasive infections such as pyogenic liver abscess in young and healthy individuals. In South Africa, limited information about the prevalence and virulence of this hvKp strain is available. The aim of this study was to determine the prevalence of hvKp and virulence-associated factors in K. pneumoniae isolates from one of the largest tertiary hospitals in a South African province. Methods. A total of 74 K. pneumoniae isolates were received from